Thermodiffusion Steffan problem in presence of convection - Kostikov , A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The Stefan thermodiffusion problem is considered, taking into account convective motions in the liquid phase. The solvability of this problem is proved in spaces of smooth functions.